IRAP-analysis for evaluating the genetic stability of endemic and endangered species of the Western Caucasus flora in the collection in vitro - I. I. Suprun; V. I. Malyarovskaya; I. V. Stepanov; L. S. Samarina (Вавиловский журнал генетики и селекции)
The characterization of genetic diversity is one of the main components of the genetic resources collection and management. Molecular markers are the most effective tool for characterizing and assessing genetic diversity in plant collections. IRAP (inter-retrotransposons amplified polymorphism) markers have proven to be some of the most effective for characterizing and evaluating germplasm, confirming the genetic fidelity of in vitro preserved cultivars and species. In this regard, the aim of this work is to test several IRAP primers to identify genetic polymorphism and study the genetic fidelity of three rare and endemic flora species of the Western Caucasus during in vitro conservation. Approbation of 16 IRAP-primers on the investigated species was carried out for Eryngium maritimum L., Galanthus woronowii Losinsk. and Campanula sclerophylla Kolak. The results made it possible to select the most efficient of them for genetic fidelity analysis of micropropagated plants. Out of 16 IRAP primers 8 amplified PCR products in Eryngium maritimum. In Galanthus woronowii as well 8 of 16 IRAP primers resulted in the amplification with the number of DNA fragments ranging from 2 to 12. In Campanula sclerophylla 9 of 16 IRAP primers amplified 1 to 11 fragments, depending on the marker. The results of the genotyping of regenerants were compared with data on stock in situ plants, which were the source of explants for in vitro conservation. In total, 60 regenerants for each species of the natural flora of the Western Caucasus were involved in the study. The results obtained demonstrated no genetic changes of the regenerants in all the studied species. These results were confirmed using ISSR analysis of an extended sample set of microplants for each species. The results obtained can serve as evidence of a low probability of genetic disorders during in vitro propagation and conservation of the species Eryngium maritimum L., Galanthus woronowii Losinsk. and Campanula sclerophylla Kolak.